Ecophysiology and molecular study of Cryptocoryne ferruginea from Sarawak - Juraidah, Salimun. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Samples of cryptocoryne ferruginea (Araceae) were collected from three identified locations: Bau-Serikin T junction, Balai Ringin and Sabal Kruin. The plants were morphologycally different among the three habitats they were found. C. ferruginea were able to survive well in 15cm water depth in this study. It also showed better growth in loam soil and after providing with 1.0 g/pot levels of fertilizer. The study also revealed that C. ferruginea under 0% and 75% shading resulted in slow growth while the best growth was observed under 50% shading. Water stress also influenced the growth of C. ferruginea. C. ferruginea could survive with placement of water at soil surface but it could not sustain watering once in every seven days.